Sufism Approach Management in Fostering Students' Noble Morals - Supriatna, Supriatna; Ulfiah, Ulfiah; Hanafiah, Hanafiah; Karim Fatkhullah, Faiz (International Journal of Educational Research & Social Sciences, 2022)
This research is based on the problem that the social conditions that occur in the community greatly affect life at school, either directly or indirectly, not only in high-level schools. The problems include violations of the norms prevailing in society. The problems that are often encountered are the presence of students who lack respect for the teacher, brawls, violence between other students, fornography and so on. Another thing that is considered to be an influence on student development is the progress of technology and information today, especially the use of social media, infiltration because the maturity and mental readiness of students has not been balanced. Therefore, the implementation of moral development is starting to become a necessity in educational institutions, in finding solutions. This research aims to identify and analyze: (1) Planning, (2) Organizing, (3) Implementation, (4) Supervision, (5) Obstacles in implementation and (6) Solutions to the problem of implementing the Sufism approach in fostering the noble character of junior high school students. This research uses a qualitative approach with a case study method. Data was collected by using triangulation techniques using interviews, document studies, and field observations. The research location is SMP Plus Darussurur and SMP Raodlotul U'lum Bandung. The research subjects were the principal, the head of the plus program and the head of the boarding school and teachers. Analysis is done through data reduction, data presentation, and conclusion drawing. Four important foundations used in this research include theological, philosophical, 6 (six) value systems and theoretical foundations. Then the theory underlying this research is the theory of management, noble character and the theory of tawasuf. The conclusion from this research is that the management approach of Sufism habituation in fostering noble character has been well programmed and shows that there is a common perception from the foundation leadership, school principals, and teachers and students, but in its implementation it has not been effective because it is still found that student behavior is not appropriate. with the demands of the noble character of students.